El aprendizaje basado en problemas : una estrategia de enseñanza y aprendizaje para promover la comprensión lectora en inglés (2017)
The present study intends to transform my pedagogical practice through the implementation of Problem Based Learning (PBL) in order to promote reading comprehension in English among the students of eleventh grade at a public high School in Bogotá. PBL was implemented as a teaching-learning strategy focused on a shared research between the teacher and 42 students, divided in 7 groups of 6 members, aimed at promoting reading comprehension and specifically reading to learn. The results derived from a diagnostic test and an initial survey produced the first reflection; subsequently, a methodological design based on Participatory Action Research was developed along four cycles. The instruments used were the students? reflection journal, teacher journal a semistructured interview and an evaluation of the tutor. Data were analyzed applying open, axial, and selective coding and also through the triangulation of the instruments. The mean themes identified in the analysis were: a) The characteristics of PBL; b) Strategies and support resources for reading comprehension and c) The transformation of the teacher role. The results suggest that the use of PBL contributed to consolidate the flexibility and Word attack skills reading strategies, developing collaborative, cooperative and self-regulated learning through the teamwork of students. Also, this approach helped to change my traditional role as the authority into the tutor role, where students embraced an active role, building relationships of equality and participation. KeyWords: Problem Based Learning (PBL), English Reading Comprehension, Strategies of reading and teacher.